Establishment of a gnotobiotic pig model of Clostridioides difficile infection and disease - Nyblade, Charlotte; Parreño, Gladys Viviana; Zhou, Peng; Hensley, Casey; Oakes, Vanessa; Mahsoub, Hassan M.; Kiley, Kelsey; Frazier, Maggie; Frazier, Annie; Zhang, Yongrong; Feng, Hanping; Yuan, Lijuan (BioMed Central, 2022)
Clostridioides difficile (C. difficile) is a gram-positive, spore-forming, anaerobic bacterium known to be the most common cause of hospital-acquired and antibiotic-associated diarrhea. C. difficile infection rates are on the rise worldwide and treatment options are limited, indicating a clear need for novel therapeutics. Gnotobiotic piglets are an excellent model to reproduce the acute pseudomembranous colitis (PMC) caused by C. difficile due to their physiological similarities to humans and high susceptibility to infection. Here, we established a gnotobiotic pig model of C. difficile infection and disease using a hypervirulent strain. C. difficile-infected pigs displayed classic signs of C. difficile infection, including severe diarrhea and weight loss. Inoculated pigs had severe gross and microscopic intestinal lesions. C. difficile infection caused an increase in pro-inflammatory cytokines in samples of serum, large intestinal contents, and pleural effusion. C. difficile spores and toxins were detected in the feces of inoculated animals as tested by anaerobic culture and cytotoxicity assays. Successful establishment of this model is key for future work as therapeutics can be evaluated in an environment that accurately mimics what happens in humans. The model is especially suitable for evaluating potential prophylactics and therapeutics, including vaccines and passive immune strategies.